2018
DOI: 10.1186/s12864-018-4697-7
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional promoters exhibit characteristic chromatin modification signature associated with transcription elongation in both sense and antisense directions

Abstract: BackgroundIn contrast to unidirectional promoters wherein antisense transcription results in short transcripts which are rapidly degraded, bidirectional promoters produce mature transcripts in both sense and antisense orientation. To understand the molecular mechanism of how productive bidirectional transcription is regulated, we focused on delineating the chromatin signature of bidirectional promoters.ResultsWe report generation and utility of a reporter system that enables simultaneous scoring of transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…LncRNA transcription from a bidirectional promoter often impacts the expression of neighboring PCGs by modifying the local chromatin structure and affecting its accessibility. 40,90,91 By analyzing the ChIP-seq and ATAC-seq from the ENCODE 3 project ( Figure 5Q), we found that the histone modification markers such as H3K4me2, H3K4me3, H3K27ac, and H3K9ac exhibit bimodal enrichment around the overlapping promoter region of the lncRNA-MAP3K4/ MAP3K4 pair, as characteristic of bidirectional promoters. 40,43 In addition, ATAC-seq and Dnase I hypersensitivity (HS) show a signal peak around this promoter region, suggesting open and accessible chromatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNA transcription from a bidirectional promoter often impacts the expression of neighboring PCGs by modifying the local chromatin structure and affecting its accessibility. 40,90,91 By analyzing the ChIP-seq and ATAC-seq from the ENCODE 3 project ( Figure 5Q), we found that the histone modification markers such as H3K4me2, H3K4me3, H3K27ac, and H3K9ac exhibit bimodal enrichment around the overlapping promoter region of the lncRNA-MAP3K4/ MAP3K4 pair, as characteristic of bidirectional promoters. 40,43 In addition, ATAC-seq and Dnase I hypersensitivity (HS) show a signal peak around this promoter region, suggesting open and accessible chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, histone modification markers mentioned above exhibited bimodal accumulation with a trough shape in the overlapping promoter region, which is characteristic of the bidirectional promoters region in ChIP-seq analysis. 40,43 DNase I HS was also enriched around this region, suggesting a chromatin structure modification, and ATAC-seq data showed open chromatin opening in this promoter region ( Figure 5Q). Collectively, consistent with other examples of lncRNA-mRNA pairs sharing a bidirectional promoter, 35,38,56 our experimental studies indicate that the overlapping promoter region of MAP3K4 and lncRNA-MAP3K4 is a bidirectional promoter, and our results confirm lncRNA-MAP3K4 regulates MAP3K4 expression in cis.…”
Section: Lncrna-map3k4 Transcribed From a Shared Bidirectional Prommentioning
confidence: 90%
“…Additional experimental studies using novel methods, including high-throughput assays ( 63 ) are required for the better understanding of the architecture and cis-regulatory elements of GLA and HNRNPH2 . Furthermore, investigation into the role of chromatin ( 64 ) on the transcriptional status of the two genes may be required. Another limitation to the present study is the lack of tissues or cells from patients with FD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some of bidirectional genes are often associated with functions in DNA repair, with the potential to participate in the development of cancer (Adachi & Lieber, 2002; Koyanagi et al, 2005; Yang, Koehly & Elnitski, 2007). Previous studies indicated that bidirectional gene pairs are associated with several genomic regulatory features such as CpG island methylation and histone modification (Adachi & Lieber, 2002; Jangid et al, 2018; Lin et al, 2007; Shu et al, 2006; Trinklein et al, 2004).…”
Section: Introductionmentioning
confidence: 99%